Homo Ludens, Aksi-Drama, Film Ek HOMO LUDENS & PINK PASTEL; AKSI DRAMA DALAM FILM EKSPERIMENTAL DENGAN PENDEKATAN ABJECT ART - Eka Wahyu Primadani, Eka Wahyu Primadani; Fossy Biosa, Sito; Waret Khunacharoensap (Program Studi Desain Komunikasi Visual, 2024)
Abstract art has penetrated the world of film. Taboo things and disgusting actions are present forcing the spectators to enjoy them with this statement of art movement. This phenomenon emerged and art writers studied it, until they succeeded in drawing a common thread about the relationship between Homo Ludens (playing humans), drama and film with artistic research (based on artistic practice); example: drama and action-acting always have cases that are never finished being discussed in film works, especially in the experimental film movement. Things that arise from the